Indonesian Local Wisdom: Reading Materials to Develop Students Character Education and 4C Skills - Sulistyani Sulistyani; Khoiriyah Khoiriyah (English Teaching Journal : A Journal of English Literature, Language and Education, 2025)
This study looked at how local wisdom reading materials in Indonesia support character education and the four Cs of the 21st century: creativity, critical thinking, teamwork, and communication. The study is classified as library research and uses a descriptive qualitative methodology. The "Bahasa Inggris" book was the study's subject, and reading texts and reading activities in it were described using a content analysis. Content analysis worksheets are intended to gather information and identify the 4Cs and character education values that can be found in the reading sections of the textbook under review. The investigation's conclusions indicate that there is a small quantity of local wisdom in the reading materials that merits more research.